2010
DOI: 10.1001/archoto.2010.183
|View full text |Cite
|
Sign up to set email alerts
|

Otologic Features in Children With Primary Ciliary Dyskinesia

Abstract: Despite continuous antibiotic therapy, the middle ear condition in PCD remained severe throughout childhood, with improvement only after age 18 years. Armstrong grommet placement did not improve the middle ear condition. Central complex defect is a marker of severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 18 publications
4
67
0
5
Order By: Relevance
“…Advocates of tympanostomy (ventilation) tubes suggest that hearing may be improved (long term) in some patients, and otorrhea can be controlled (97). In contrast, the European Respiratory Society Consensus Statement recommends against placement of tubes for chronic otitis media in patients with PCD, because resultant otorrhea is a problem, and spontaneous resolution of chronic otitis media may occur in the teenage years (3,98). Episodes of otitis media should be treated by standard approaches, but data are not available to address the question of surgical intervention.…”
Section: Management Of Otolaryngologic Manifestations Middle Ear Diseasementioning
confidence: 99%
“…Advocates of tympanostomy (ventilation) tubes suggest that hearing may be improved (long term) in some patients, and otorrhea can be controlled (97). In contrast, the European Respiratory Society Consensus Statement recommends against placement of tubes for chronic otitis media in patients with PCD, because resultant otorrhea is a problem, and spontaneous resolution of chronic otitis media may occur in the teenage years (3,98). Episodes of otitis media should be treated by standard approaches, but data are not available to address the question of surgical intervention.…”
Section: Management Of Otolaryngologic Manifestations Middle Ear Diseasementioning
confidence: 99%
“…Almost all patients with PCD will experience at least 1 episode of otitis media by the age of 5 years with reoccurrences by the age of 17 years. Without findings of otitis media, the physician should doubt the diagnosis of CF rather than PCD [14]. Variable manifestations of auditory tract infections with chronic secretory otitis media, middle ear fluid, tympanic membrane perforation and otorrhea which may persist in PCD are not found in CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical tympanostomy tubes were inserted because of hearing loss due to effusions in middle ear. Tympanostomy in PCD patients should be performed according to a cost beneficial assessment on the degree of hearing loss and the outcomes such as otorrhea and tympanic membrane perforation [14]. Infertility, as a complication of PCD due to flagella defects and immotility of sperms is more prominent in males.…”
Section: Discussionmentioning
confidence: 99%
“…However, a direct comparison between management strategies was not possible as patients with worse baseline hearing thresholds systematically received surgical intervention. PRULIÈRE-ESCABASSE et al [72] observed a decrease in acute otitis media and an increase in chronic otitis media with age. Persistent otitis media with effusion was prevalent (over 80%) throughout all age groups.…”
Section: Upper Airway Managementmentioning
confidence: 96%